Pathology and surgery around the vertebral artery - George, Bernard; Bruneau, Michael; Spetzler, Robert F. (Paris Springer, 2011)
This is the first comprehensive book about surgery on and around the vertebral artery all along its cervical and intracranial course. This vessel has been considered for long as out of surgical reach leaving many different pathologies not or incompletely treated. The surgical exposure and control of the vertebral artery not only permit to treat lesions of the vertebral artery wall or developed in contact to it but also to improve the access to the intervertebral foramen (tumors, osteophytes), to the anterior aspect of the spinal cord (tumors, spondylotic spurs), to the foramen magnum and to the jugular foramen. This book written by leading experts includes all aspects of vertebral artery surgery from anatomy to imaging, surgical techniques and pathologies; it is illustrated by many figures especially operative views and schematic drawings so that the beginner as well as the experienced surgeon find useful information. One of the editors of this book (B. GEORGE) was recently awarded the Olivecrona award for his work on the surgery of the vertebral artery.
Electronic reproduction.
Keywords: Operations, surgical